Analisis Situation Awareness pada Unit Apron Movement Control (AMC) di Bandar Udara Wamena, Papua - Panggalo, Trialwi; Jumlad, Walid (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Situation Awareness is an important factor in influencing someone when making a decision. The AMC unit is carrying out their duties, of course the AMC unit has several obstacles and problems that can affect Situation Awareness of officers, regarding this the unit will provide good service in accordance with existing SOPs. This research was conducted with the aim of knowing the implementation and efforts made to increase Situation Awareness at the AMC unit at Wamena Airport. In this research, using a descriptive qualitative in which includes primary data and secondary data. The primary data in this research included the results of observations and interviews conducted at the Wamena Airpor AMC unit. Mainwhile secondary data is taken using indirect data sources such as literature review and previous research references. From the results of this observation is known that the Situation Awareness possessed by AMC officers at Wamena Airport is already at the highest level, specifically level 3, cause officers can properly and effectively understand work situations in the field and in the office, and are able to understand applicable rules and when a problem occurs, they will directly observe and coordinate with other units. What the AMC unit has done in increasing Situation Awareness at Wamena Airport has been good at handling duties and responsibilities. Guidelines for officers in carrying out their duties every day always follow and learn the latest regulations. Even though carrying out their duties with limited facilities, AMC officers are able to provide services in the apron area to the maximum extent possible and of course following established procedures and regulations and being aware of situations that have not yet occurred andare currently occurring. Keywords : situation awareness, level scale, apron movement control.